Employees Perception on Corporate Social Responsibility Practices and Affective Commitment - Ahmed, Nurulatika; Tahir, Nor Suziwana (Universitas Syiah Kuala, 2019)
AbstractObjective This research aims to study the employees perception on CSR practices and affective commitment in public listed companies in the area of Klang Valley, Malaysia. There were four dimensions on CSR practices that might affect the employees affective commitment in the organization which are economic responsibility, legal responsibility, ethical responsibility and philanthropic responsibility.Design/methodology This study used Likert-Scale questions in order to answer both dependent and independent variables. A set of questionnaire was distributed to the employees who works in public listed companies in Klang Valley area regardless of their industry as population of this study. The data were analyzed by using Statistical Package for the Social Sciences (SPSS).Results The findings from this study reveal that there is significant relationship of the employees perception on four dimensions of CSR practices and affective commitment. More than that, between all the four dimensions of CSR practices, economic responsibilities are found as the main element in influencing the employees affective commitment in work. The findings also show that role of gender does not moderate any relationship between dependent variables and independent variables.Research limitations/implications This research adds the information on the level of affective commitment towards employees perceptions in the public listed companies in Malaysia as theoretical part that focused on the CSR dimensions based on the Carroll s Model which are economic responsibility, legal responsibility, ethical responsibility and philanthropic responsibility with gender as the moderating variable in the study. The empirical part of this study has assessed that the economic, legal, ethical and philanthropic responsibility that can affect the level of affective commitment towards the employees perceptions in the public listed companies in the Klang Valley.